2021
DOI: 10.1017/s0954102021000316
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton diversity in two different Antarctic lakes assessed using metabarcoding

Abstract: Antarctic lakes have generally simple periphyton communities when compared with those of lower latitudes. To date, assessment of microbial diversity in Antarctica has relied heavily on traditional direct observation and cultivation methods. In this study, sterilized cotton baits were left submerged for two years in two lakes on King George Island and Deception Island, South Shetland Islands (Maritime Antarctic), followed by assessment of diversity by metabarcoding using high-throughput sequencing. DNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The internal transcribed spacer 2 (ITS2) of the nuclear ribosomal DNA was used as a DNA barcode for molecular species identification [ 27 , 33 , 34 , 35 ]. PCR amplicons generated using the universal primers ITS3 and ITS4 [ 36 ] were sequenced commercially by Macrogen Inc. (Seoul, Republic of Korea) using high-throughput paired-end sequencing (2 × 300 bp) on a MiSeq System (Illumina, San Diego, CA, USA), using the MiSeq Reagent Kit v3 (600 cycles).…”
Section: Methodsmentioning
confidence: 99%
“…The internal transcribed spacer 2 (ITS2) of the nuclear ribosomal DNA was used as a DNA barcode for molecular species identification [ 27 , 33 , 34 , 35 ]. PCR amplicons generated using the universal primers ITS3 and ITS4 [ 36 ] were sequenced commercially by Macrogen Inc. (Seoul, Republic of Korea) using high-throughput paired-end sequencing (2 × 300 bp) on a MiSeq System (Illumina, San Diego, CA, USA), using the MiSeq Reagent Kit v3 (600 cycles).…”
Section: Methodsmentioning
confidence: 99%
“…The internal transcribed spacer 2 (ITS2) of the nuclear ribosomal DNA was used as a DNA barcode for molecular species identification [13][14][15][16]. PCR amplicons generated using the universal primers ITS3 and ITS4 [17] were sequenced commercially by Macrogen Inc. (South Korea) using high-throughput paired-end sequencing (2 × 300 bp) on a MiSeq System (Illumina), using the MiSeq Reagent Kit v3 (600 cycles) and following the manufacturer's protocol.…”
Section: Dna Extraction Library Construction and Sequencingmentioning
confidence: 99%
“…The main routes proposed for such dispersal include (i) the American pathway, with dispersal via the Neotropics and Patagonia to sub-Antarctic South Georgia and maritime Antarctica, (ii) the African pathway via the East and Central African Mountains to sub-Antarctic islands such as Marion Island and the Kerguelen archipelago, and (iii) the Indomalayan-Malesian pathway from south-east Asia to southeast Australia, New Zealand, and associated islands (Ochyra et al, 2008). Molecular data have recently supported the bipolarity of several moss taxa (Biersma et al 2017;overview in Câmara, Carvalho-Silva, Pinto, et al, 2021;Câmara, Convey, Rangel, et al, 2021;Câmara, De Souza, Pinto, et al, 2021). Muñoz et al (2004) showed the importance of air currents as an LDD mechanism in the Southern Hemisphere for non-flowering plant species distributions, demonstrating a pattern of diaspore transfer from South America towards Africa at mid latitudes.…”
Section: Introductionmentioning
confidence: 97%